Sistem Informasi Geografis untuk Menentukan Rute Lokasi Wisata Danau Toba dengan Metode Simulated Annealing - Nur Sartika BR Ginting; NM Faizah; Widyat Nurcahyo (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
Tourist sites are a natural sector in the development of economic, business, social and environmental qualities in a country. In various aspects, the growing potential of tourist sites can also have an impact on most developing countries. If a tourist location is developed, modern and maintained, it can provide more value for a country. The purpose of this research is to make it easier for visitors to find tourist sites that they don't know about around Lake Toba and make it easier for them to find routes for tourist locations they want to visit. Making available tourist sites more widely known by tourists, as well as culinary and typical souvenirs from these tourist attractions are also known to tourists. The Simulated Annealing algorithm can provide the closest route from several tourist location points and is implemented in making geographic information system applications. The results of the study in the form of a geographic information system application to determine the route to the tourist location of Lake Toba with the Simulated Annealing method can help tourists to determine the route of tourist sites that they have not yet explored and make it easier for them to go to the location they want to visit so that they can save time on their way.